The Foreign Trade of the United States from 1820 to 1840 - Sterns, Worthy Putnam (Journal of Political Economy, 1900)
TilE export of first importance during the third decade of the century was cotton. Its value for the ten years was 256 million dollars. This was 48 per cent. of the total value of domestic exports and 44 per cent. of the value of all imports retained for home consumption.